Efeito da potencialização do ácido glicólico na remoção de Smear Layer e erosão na dentina radicular - Soldin, Luara Presser (2020)
Objectives: to comparatively evaluate the influence of glycolic acid (AG) and EDTA potentiation with EasyClean (EC) and passive ultrasonic irrigation (PUI) in the removal of smear layer and erosion in root dentin. Methods: distal-labial canals of 80 upper molars were prepared with the ProTaper Next (N=80). Afterwards, they were longitudinally fractured to allow the quantification of the smear layer created in the cervical, middle and apical thirs of the roots, using scanning eléctron microscopy (SEM). After reassembling the fractured root halves, they were divides into 8 goups according to different final irrigation solutions (n=10): distilled water (AD), EDTA 17%, AG 10% and AG 17%; and irrigatin activation techniques: EC in reciprocating movement for 3 cycles of 20s and PUI also for 3 cycles of 20s. After irrigation, the teeth halves were separated again to obtain images in the same areas as the first SEM evaluation. The percentage of smear layer removal in the irrigated areas was obtained in relation to the percentage of the total area by processing the generated images in the Image J software. The smear layer removal data were submitted to ANOVA and Bonferroni tests (α = 0,05). The dentin erosion scores were analyzed by Kruskal-Wallis and Tukey (α = 0,05). Results: the highest percentage of smear layer removal in all groups was found in AG 10 and 17% activated with EC (P<0,05). When activated with PUI, there was no statistically significant difference between EDTA 17%, AG 16 10% and AG 17% (P<0,05). The EDTA and AG solutions in both concentrations, activated with EC and PUI, did not cause erosion in the root dentin. Conclusion: the AG was effective for the smear layer removal in both thirds of the root canals when potentiation methods were used and there was no occurrence of dentin erosion.